2010
DOI: 10.1007/s10802-010-9472-4
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Experience of Male High School Students with ADHD

Abstract: This study compared the high school academic experience of adolescents with and without childhood ADHD using data from the Pittsburgh ADHD Longitudinal Study (PALS). Participants were 326 males with childhood ADHD and 213 demographically similar males without ADHD who were recruited at the start of the follow-up study. Data were collected yearly from parents, teachers and schools. The current study used assessment points at which the participants were currently in or had recently completed grades 9, 10, 11, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
196
2
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(218 citation statements)
references
References 39 publications
8
196
2
12
Order By: Relevance
“…High school students with ADHD are also significantly more likely to be absent or tardy and are more than eight times more likely to drop out of school than their peers without ADHD [13]. They are significantly more likely to withdraw from a course [11].…”
Section: Discussionmentioning
confidence: 99%
“…High school students with ADHD are also significantly more likely to be absent or tardy and are more than eight times more likely to drop out of school than their peers without ADHD [13]. They are significantly more likely to withdraw from a course [11].…”
Section: Discussionmentioning
confidence: 99%
“…D'ailleurs, il faut spécifier que ces résultats concernent uniquement les étudiants ayant un TA ou un TDA/H qui ont réussi à accéder aux études postsecondaires et que, de ce fait, tous ceux qui n'ont pas poursuivi leurs études ne sont pas considérés par l'étude. Or, l'hyperactivité et l'inattention sont considérées comme des facteurs de risque importants du décrochage scolaire (Gregg, 2009 ;Kent et al, 2011 ;Pica, Plante et Traoré, 2014 ;Vitaro, Brendgen, Larose et Tremblay, 2005). Les travaux de Barkley, Murphy et Fischer (2008) indiquent que les personnes ayant un TDA/H ont moins de chance de poursuivre des études postsecondaires que leurs pairs.…”
Section: Problématiqueunclassified
“…Their review also suggested that students with ADHD were more likely to be identified as having learning disabilities and to be grade-retained. Nevertheless, the effects of ADHD on standardized scholastic achievement tasks remain after controlling for general intellectual ability and co-morbid deficits in cognitive function (Alloway, 2009;Kent et al, 2011;Mayes & Calhoun, 2006). The effects of ADHD are also more pronounced for some areas of learning than for others.…”
Section: Introductionmentioning
confidence: 99%